Concise introduction to logic and set theory - Jebril, Iqbal H.; Dutta, Hemen, 1981-; Cho, Ilwoo (Boca Raton : SRC Press, 2022)
"This book deals with two important branches of mathematics, namely, logic and set theory. Logic and set theory are closely related and play very crucial roles in the foundation of mathematics, and together produce several results in all of mathematics. The topics of logic and set theory are required in many areas of physical sciences, engineering, and technology. The book offers solved examples and exercises, and provides reasonable details to each topic discussed, for easy understanding. The book is designed for readers from various disciplines where mathematical logic and set theory play a crucial role. The book will be of interested to students and instructors in engineering, mathematics, computer science, and technology"--
Includes bibliographical references (page 157) and index.
Keywords: Logic, Symbolic and mathematical; Set theory